Clinical value of myocardial performance index in patients with isolated diastolic dysfunction - José Maria Gonçalves Fernandes (Cardiovascular Ultrasound, 2019)
Abstract Aims The Doppler-derived myocardial performance index (MPI) has been considered as a diagnostic and prognostic Doppler marker for many different clinical conditions. The purpose of this study was to determine the diagnostic accuracy of traditional Pulsed-wave Doppler (PWD-MPI) and Pulsed-wave tissue Doppler imaging (TDI-MPI) and the degree of agreement between these methods in patients with grade-I diastolic dysfunction (DDI) and a normal ejection fraction. Methods Forty-seven consecutive ambulatory patients with DDI were compared to 51 healthy subjects with normal echocardiograms. All subjects underwent measurement of time intervals and MPI with PWD and pulsed TDI. Results TDI-MPI and PWD-MPI were significantly higher in patients with DDI than in control subjects: 0.49 ± 0.14 vs. 0.40 ± 0.09 (P < 0.001) and 0.45 ± 0.11 vs. 0.37 ± 0.08 (P < 0.001), respectively. Cutoff values of TDI-MPI > 0.42 and PWD-MPI > 0.40 identified DDI subjects, with sensitivities of 74 and 64%; specificities of 61 and 69%; positive likelihood ratios of 1.9 and 2.0; and negative likelihood ratios of 0.42 and 0.53, respectively; no significant difference was noted between the areas under the ROC curves of TDI-MPI and PWD-MPI (P = 0.77). Bland-Altman plots showed wide limits of agreement between these indices: − 0.17 to 0.23 in healthy subjects and − 0.24 to 0.32 in DDI patients. Conclusion PWD-MPI and TDI-MPI showed poor clinical agreement and were not reliable parameters for the assessment of left ventricular diastolic function.